Exploring a collaborative model using grounded theory: a case study of a digital healthcare service platform - Zhao, Lin; Sity Daud,; Mohd Rizal Yaakop, (Penerbit Universiti Kebangsaan Malaysia, 2025)
“Government as a Platform” (GaaP) has been widely accepted. However, a government alone cannot ensure the establishment and smooth operation of digital service platforms. Therefore, this study aims to explore the role of different stakeholders and their collaboration mechanisms concerning the establishment and operation of a digital service platform. Using the “Zhenghaoban” digital service platform on healthcare in Zhengzhou, China, as a case, this study finds four factors that facilitate the collaboration among the government, enterprises, social organizations and health sectors. The four factors are the strong planning and collaborative capability of the government; good integration capability of policy, technology and services of health sectors; strong capability in technology integration, innovation and security protection of enterprises; good facilitating and coordinating capabilities of social organizations. This grounded theory study contributes to the literature on government digital service platforms by proposing a collaborative multi-stakeholder model, offering practical insights for local e-governments seeking to enhance their governance capacity through diverse digital platforms.